Composting of Rice Straw–Based Materials using Aerobic Bioactivator Isolated from Rice Straw, Mahogany Bark and Cassava Peels - Vita Ratri Cahyani; Rahayu Rahayu; Kynthavi Paramitha Lakshitarsari; Rahma Amira Zhalzhabila Wakak Megow; Nadine Yuki Azzahra (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Compost is one of organic fertilizers that play an important role in maintaining soil health and supporting sustainable agriculture. Diverse aspects could be developed to increase the quality of compost. This study aims to compare the quality of compost produced by using two different bioactivators, namely aerobic bioactivator RMC (the microbial consortia isolated from composted rice straw, mahogany bark and cassava peels + additional supplement) and fermentative bioactivator (EM4 + molasses) in the composting of the mainly rice straw-based materials. Composting was conducted using a single factor completely randomized design consisting of five levels as follows: C0 (control, rice straw); C1 (rice straw + bioactivator EM4 + molasses); C2 (rice straw + bioactivator RMC + additional supplement); C3 (rice straw + cow dung + bioactivator RMC + additional supplement); C4 (leaf litter + cow dung + bioactivator RMC + additional supplement, as comparison treatment with no rice straw). Among the treatments of C0, C1 and C2, composting the same rice straw material but different bioactivators, C2 showed the highest compost quality and decomposition rate. Among the other three treatments of C2, C3 and C4 composting different materials but using the same bioactivator, C3 showed the highest compost quality, but the three treatments showed the same high decomposition rate. Based on the characteristics of the compost product, including nutrient content, the treatment C3 produced the highest quality, followed by C4 and then C2. Both bioactivators EM4 + molasses and RMC+ additional supplement tended to increase total bacteria, fungi, nitrogen-fixing bacteria and phosphate-solubilizing microbiota in the compost products compared to the control without bioactivator. A set of aerobic bioactivator RMC plus additional supplement serve as one strategy to accelerate the composting process and to enhance the compost quality.